Human Factor Analysis of Light Emitting Diode Technologies for Cabin Lighting in Manned Space Flight Applications - Treichel, Todd H. (Proceedings of the Wisconsin Space Conference, 2015)
Advantages of transitioning to Light emitting diode (LED) technologies in spacecraft are reduced mass, reduced occupied volume, reduced power, improved color control, longer operating life, and lower cost associated with power consumption and disposal. According to Brainard et al (2012) newly designed U.S. spacecraft, and ISS fluorescent tube replacements, must utilize LEDs in lieu of traditional artificial light sources to take advantage of technology improvements. Light emitting diode technologies remain a controversial technology in the aerospace industry, where commercial manufacturers are the only source for procurement. The first portion of this research effort was performed to investigate commercially manufactured LEDs, by measuring light output quality to see if the LEDs will meet NASA and DOD reliability requirements. The second portion of the research pertains to this paper for 2014 which applies to LEDs with the highest reliability from the first portion of the this research. A randomized block design has been constructed for evaluating human factor effects using soft white light, emitted from LEDs and a NASA qualified ISS fluorescent.